INTERRELATIONSHIP OF NETWORKS, KNOWLEDGE, AND PERFORMANCE OF BUSINESSES THROUGH THE LENS OF COASTAL DESTINATION DEVELOPMENT - Azinuddin, Muaz; Mior Shariffuddin, Nur Shahirah; Mat Som, Ahmad Puad; Muhammad Salim, Muhammad Arfin; Eppang, Buntu Marannu (PLANNING MALAYSIA, 2023)
The sustainable future of coastal destination development is mainly reliant on performance of small and medium sized tourism enterprises (SMTEs) since they are the main catalyst of tourism growth. Given SMTEs’ operational sizes, the need to enhance their knowledge base through their networks to stay competitive is heightened. This research examines how the absorptive capacity (AC) affects the dynamic between formal and informal networks and business management performance of SMTEs. The study focuses on four sub-sectors in Terengganu, Malaysia: hotels and resorts, travel agencies, restaurants, and handicrafts. The study analysed survey data from 119 entrepreneurs using a hierarchical regression model. The results showed that the nexus between the use of formal networks and business management performance is significantly mediated by AC, while no significant relationships were found with the use of informal networks. The study emphasizes the importance of formal actors in promoting knowledge flows and enhancing coastal destination development and competitiveness.